2011
DOI: 10.1093/hmg/ddr589
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-specific effect of chromosome 1q21.1 rearrangements and GJA5 duplications in 2436 congenital heart disease patients and 6760 controls

Abstract: Recurrent rearrangements of chromosome 1q21.1 that occur via non-allelic homologous recombination have been associated with variable phenotypes exhibiting incomplete penetrance, including congenital heart disease (CHD). However, the gene or genes within the ∼1 Mb critical region responsible for each of the associated phenotypes remains unknown. We examined the 1q21.1 locus in 948 patients with tetralogy of Fallot (TOF), 1488 patients with other forms of CHD and 6760 ethnically matched controls using single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
120
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 42 publications
9
120
1
2
Order By: Relevance
“…Of the 31 relatives with 1q21.1 duplications, 26 were transmitting parents and five were siblings. The 76 probands (including adults and children) comprised 70 subjects ascertained because of major clinical features, five reported in nonoverlapping control populations, 2,5,6 and one parent of a child with autism spectrum disorder where the child did not have a 1q21.1 duplication. 22 The majority were referred from centers in Europe or the United States.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 31 relatives with 1q21.1 duplications, 26 were transmitting parents and five were siblings. The 76 probands (including adults and children) comprised 70 subjects ascertained because of major clinical features, five reported in nonoverlapping control populations, 2,5,6 and one parent of a child with autism spectrum disorder where the child did not have a 1q21.1 duplication. 22 The majority were referred from centers in Europe or the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Soemedi et al 5 identified 1q21.1 duplications in 3 of 10,910 (0.027%) individuals originating from multiple source cohorts. Two were from the Wellcome Trust Case-Control Consortium 2 control cohort of 5,919 (0.034%) adults from the 1958 British Birth Cohort and the UK Blood Service (http://www.wtccc.org.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations